DOES PAID PROMOTE INFLUENCES USER FREQUENCY TO PURCHASE? AN ANALYSIS USING AIDA DIMENSION - Muhammad Choiri Ikhsan; Vina Sri Astuti; Abdul Agung Wijaya; Firdaus Finuliyah; Ahmad Miskatul Qulub (Airlangga Journal of Innovation Management, 2022)
The purpose of this study is to determine how paid promote program in Instagram could influence user intention to purchase products of fashion, culinary and craft products that dominate. The method used is a descriptive analysis using Attention, Interest, Desire and Action (AIDA) dimension to measure user frequency of purchasing products promoted. Determination of the number of respondents using a survey technique of 100 respondents. Data analysis is done by recapitulating the results of filling out the questionnaire from respondents. Recapitulation is carried out with descriptive techniques to describe the facts of each of those studied. The findings are that relationship between the > 0.600 indicators and the AIDA dimension as an important construct in advertising sustainability is paid promote fashion, culinary and craft products. And the AIDA construct, namely Attention, Interest, Desire and Action, are the driving factors for the dominant frequency response 6-8 times in craft products. It can be said that paid promote can be one marketing tools for creative economic sector products. This study's implications are delivered in two sides, literature and practices. Implication for literature, this research sheds light on customer behavior research in this digital technology era, especially using social media Instagram through paid promote programs within AIDA dimension - which is not yet discussed in previous research. The practical implication of this research is it also brings an emerging development analysis of the impact of using paid promotion as one of the marketing media for the creative economy sector products.